Jewish Autobiographical Writing. Memoirs of Moses Vasertsug (c. 1760–1832) - Michałowska-Mycielska, Anna (Acta Poloniae Historica, 2024)
The article discusses the memoirs of Moses Vasertsug (c. 1760–1832) – an extremely interesting historical source, brilliantly demonstrating processes and phenomena in Jewish society at the turn of the eighteenth and nineteenth centuries. Vasertsug received a traditional religious education and performed related functions in Jewish communities, first in Pomerania (Karlino, Gryfino), and later in Greater Poland (Kórnik) and Mazovia (Płock). He continued to do so in the post-partition period, but the functions he performed took on a new, quasi-official character. The memoirs show the transformation of the previous occupations performed by the Jews, as well as the new opportunities for settlement and economic activity that opened up for them during the post-partition period. The memoirs also show that Jewish autobiographical writing is not necessarily the result of acculturation and departure from Jewish tradition.